1980
DOI: 10.1007/bf01677394
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O serotyping in different patient groups with urinary tract infections

Abstract: Using 44 anti-O sera 789 Escherichia coli strains isolated from the urine of patients with urinary tract infections were typed. Of the 119 E. coli strains from the urine of children, 49.6% were O-typable; only 3.4% were rough strains. Of 357 strains from pregnant women, 47% were O-typable; 12.1% were rough strains. The largest proportion of O-typable E. coli strains was found among 314 strains isolated from adults with recurrent urinary tract infections (55.4% of the 314 strains); 8% were rough strains. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…25 , O 75 , and O 15 to be predominantly prevalent while, serotypes O 83 and O 22 had the lowest prevalence which is similar to the studies conducted earlier in Iran and Mexico city[4,[24][25][26]. Various O-serogroups are found with variable frequencies in UTIs patients[27][28][29][30]. The present investigation also observed signi cant (p < 0.05) relation between the O 8…”
supporting
confidence: 89%
“…25 , O 75 , and O 15 to be predominantly prevalent while, serotypes O 83 and O 22 had the lowest prevalence which is similar to the studies conducted earlier in Iran and Mexico city[4,[24][25][26]. Various O-serogroups are found with variable frequencies in UTIs patients[27][28][29][30]. The present investigation also observed signi cant (p < 0.05) relation between the O 8…”
supporting
confidence: 89%
“…Totally, O25 and O15 were the most prevalent serogroups. Since 1980 [52], many investigators reported that several O-serogroups were found with variable frequencies in UTIs patients. Similar results have been reported recently too [12,53].…”
Section: Resultsmentioning
confidence: 99%